2013
DOI: 10.1007/s00520-013-2068-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chemotherapy-induced peripheral neuropathy using current perception threshold and clinical evaluations

Abstract: Purpose Chemotherapy-induced peripheral neuropathy (CIPN) is increasing with introduction of new and combination cancer pharmacotherapies. This study evaluated associations between clinical and self-report measurements and current perception threshold (CPT), a neuroselective measure of sensory nerve function that may detect asymptomatic CIPN damage. Methods Data for this secondary analysis were from a prospective, observational study using CPT to evaluate CIPN. Bivariate mixed models, accounting for the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 39 publications
2
62
0
1
Order By: Relevance
“…In the only study identified that compared patients who were CTX naïve (n=20), to patients who received CTX (n=9), 104 the mean grip strengths were 33.5 kg (±8.5) and 30.1 kg (±11.4), respectively. For both groups of patients in our study, the mean grip strengths were lower which may be related to differences in the mean age of the patients and the fact that survivors without CIN did receive CTX.…”
Section: Discussionmentioning
confidence: 99%
“…In the only study identified that compared patients who were CTX naïve (n=20), to patients who received CTX (n=9), 104 the mean grip strengths were 33.5 kg (±8.5) and 30.1 kg (±11.4), respectively. For both groups of patients in our study, the mean grip strengths were lower which may be related to differences in the mean age of the patients and the fact that survivors without CIN did receive CTX.…”
Section: Discussionmentioning
confidence: 99%
“…DTRs are a measure of the sensorimotor system, and reduced response is an indication of sensory neuropathy in the setting of OIPN. Reduced DTRs have been shown to occur in association with hypoesthesia using current perception threshold in the setting of chemotherapy-induced peripheral neuropathy 32 . We have also reported reduced vibration perception in combination with reduced DTRs using TNSc © , where DTRs were the most sensitive component of the neurological examination in chemotherapy-induced peripheral neuropathy 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Scores for the sensory, motor and autonomic scales indicated low levels of symptomatology/problems for the study participants. Elsewhere, it is reported that reduced feelings of touch and sensation associated with CIPN, reflected patients' worsening quality of life (Griffith et al, 2013).…”
Section: Discussionmentioning
confidence: 99%